2003
DOI: 10.1152/ajplung.00312.2002
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of plasminogen activator inhibitor-1 in pulmonary edema fluid are associated with mortality in acute lung injury

Abstract: -The alveolar fibrinolytic system is altered in acute lung injury (ALI). Levels of the fibrinolytic protease inhibitor, plasminogen activator inhibitor-1 (PAI-1), are too low in bronchoalveolar lavage to address its prognostic significance. This study was performed to assess whether PAI-1 antigen in undiluted pulmonary edema fluid levels can identify patients with ALI and predict their outcome. PAI-1 antigen levels in both plasma and edema fluid were higher in ALI compared with hydrostatic edema, and edema flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
198
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(213 citation statements)
references
References 53 publications
6
198
0
7
Order By: Relevance
“…Protein C was measured using a commercially available ELISA from Helena Laboratories (Beaumont, TX), as described previously (18). PAI-1 was measured using a commercially available ELISA from American Diagnostica (Stamford, CT), as previously described (19). Measurements were made in available samples from the cohort; the number of available measurements differed by biomarker, but ranged from 361 to 755.…”
Section: Biomarker Measurementsmentioning
confidence: 99%
“…Protein C was measured using a commercially available ELISA from Helena Laboratories (Beaumont, TX), as described previously (18). PAI-1 was measured using a commercially available ELISA from American Diagnostica (Stamford, CT), as previously described (19). Measurements were made in available samples from the cohort; the number of available measurements differed by biomarker, but ranged from 361 to 755.…”
Section: Biomarker Measurementsmentioning
confidence: 99%
“…Studies of animal models of VILI showed that high tidal volume ventilation increases alveolar fibrin deposition and systemic PAI-1 activity while lungprotective mechanical ventilation decreases BALF levels of PAI-1, attenuates coagulation, and enhances fibrinolysis [14,21] . Although aerosol administration offers the theoretical advantage of the lungs receiving high concentrations of tPA, we chose intravenous administration because intra-alveolar and intravascular fibrin deposition and high systemic PAI-1 levels are frequently found in the setting of acute lung injury or VILI [5,15] . Intraperitoneal tPA lavage could also reduce intraabdominal PAI-1 concentrations in experimental peritonitis [20] .…”
Section: Discussionmentioning
confidence: 99%
“…High pulmonary and systemic PAI-1 levels and increased alveolar fibrin deposition are features of animal models of VILI [14] . Increased plasma levels of PAI-1 are associated with adverse clinical outcomes and increased mortality in adults with acute lung injury [15] . tPA is responsible for fibrin degradation via the activation of plasminogen and has been used for thrombolysis in patients with acute myocardial infarction [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Ontology analysis of the candidate genes demonstrates that the major mechanical stretch-related ALI biological process was blood coagulation with genes in this ontology including fibrinogen A, coagulation factor III, plasminogen activator, urokinase receptor (uPAR), tissue factor, and PAI-1 ( Figure 3). Many of these same genes have been implicated elsewhere as potential candidate genes in ALI (13,28,29) and in VALI (30,31). In addition to coagulation, there was prominent representation of genes involved in innate immunity (MIF, CD14, TNF, IL-1RA, C5aR, IL-6).…”
Section: Cross-species Gene Expression Profiling and Identification Omentioning
confidence: 99%
“…Despite the evidence from association-based studies suggesting that genetic variation contributes to ALI susceptibility and severity (5)(6)(7)(8)(9)(10)(11)(12)(13), the genetic basis of ALI remains incompletely understood. Multiple factors contribute to the difficulty in defining the exact nature of genetic factors relevant to ALI.…”
Section: Studies Implicating a Genetic Basis For Ali Susceptibility Amentioning
confidence: 99%